2002
DOI: 10.1038/sj.ijo.0801963
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, insulin and lipid metabolism in post-menopausal women

Abstract: OBJECTIVE:To investigate relationships between body fat and its distribution and carbohydrate and lipid tolerance using statistical comparisons in post-menopausal women. DESIGN: Sequential meal, postprandial study (600 min) which included a mixed standard breakfast (30 g fat) and lunch (44 g fat) given at 0 and 270 min, respectively, after an overnight fast. SUBJECTS: Twenty-eight post-menopausal women with a diverse range of body weight (body mass index (BMI), mean 27.2, range 20.5 -38.8 kg=m 2 ) and abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 52 publications
7
27
1
1
Order By: Relevance
“…This supports findings from other groups on Caucasian subjects. 21,22,30,[45][46][47][48] However, it was observed that the Caucasian men in the present study had a significant positive associations between fasting glucose and BMI, waist and subscapular. Although the Sikh men had higher insulin resistance than the Caucasian men, they also presented with higher fasted insulin, which could have contributed to the lack of relationship between glucose and body fat distribution.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This supports findings from other groups on Caucasian subjects. 21,22,30,[45][46][47][48] However, it was observed that the Caucasian men in the present study had a significant positive associations between fasting glucose and BMI, waist and subscapular. Although the Sikh men had higher insulin resistance than the Caucasian men, they also presented with higher fasted insulin, which could have contributed to the lack of relationship between glucose and body fat distribution.…”
Section: Discussioncontrasting
confidence: 51%
“…A limitation of this study was that a direct measure of body fat topography was not completed due to cost and availability of equipment; therefore, waist circumference was used as an index of central fat, which our group 30,48 and others 70,71 have identified as the most appropriate surrogate measure. Waist circumference has emerged as the strongest correlate to both the degree of obesity and accumulation of visceral adipose tissue, when anthropometric data were compared with direct imaging techniques in Caucasians, 70,71 yet to date it has not been determined whether this is the case in Indian Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies are performed in young male adults, especially students. Studies that have compared young and middle aged subjects reveal marked effects of age on postprandial lipaemia (Jackson et al, 2003) Few of the early studies were performed in women, although recently studies have been specifically performed in female subjects (Murphy et al, 1995;Mekki et al, 1999;Lovegrove et al, 2002) to alleviate the lack of information in relation to sex differences. It is noteworthy that for a given meal, the postprandial lipid response is lower in women than men, owing to a higher clearance capacity (lipoprotein lipase activity).…”
Section: Healthy Subjectsmentioning
confidence: 99%
“…Given the complexity of this syndrome involving insulin resistance, great care should be given to selection of subjects because of their metabolic heterogeneity. Some studies have been performed in obese/insulin-resistant subjects (Jeppesen et al, 1994;Couillard et al, 1998;Mekki et al, 1999;Guerci et al, 2000;Lovegrove et al, 2002;Harbis et al, 2004).…”
Section: Subjects At Disease Risk or Patientsmentioning
confidence: 99%
“…This type of postprandial protocol has been used to determine (a) the effect of chronic dietary fat manipulation or cereal/non-digestible carbohydrate supplement on the postprandial lipaemic response (studies 1-6, n = 257 subjects) [3,10,24,26,28], (b) influence of body size and shape on the postprandial lipaemic response (study 7, n = 28 subjects) [27,39] and (c) the acute impact of specific meal fatty acids in the first meal on the postprandial response to the second meal (studies 8 and 9, n = 20 subjects) [16][17][18][32][33][34]. An overview of the study designs are shown in Fig.…”
Section: Sequential Test Meal Protocolsmentioning
confidence: 99%